A case control study on risk factors for stroke among Filipinos the PNA-DOH RIFASAF project - Roxas, Jr., Artemio A.
Stroke is the third leading cause of death worldwide. In the Philippines, it belongs to the second leading cause of death and a main cause of prolonged disability but is also one of the most preventable among the disastrous diseases. The WHO has predicted that cardiovascular diseases, which include Stroke and Coronary Heart Disease, will be an epidemic by year 2020. The availability of valid local data can be very useful in clinical practice, health policy making and resource allocation. "What you don't measure, you cannot efficiently change". This study is the response to the challenge of The Melbourne Declaration in providing local stroke data.The objective of this study is to determine risk factors for stroke among Filipinos.Multicenter, multiregional hospital-based 1:1 matched case-control studyFifty-five hospitals located in 13 of the 16 administrative regions of the Philippines where 32 fellows of the Philippine Neurological Association are with active medical practice.Over 5 months, 1922 patient consisting of 961 stroke cases with 961 sex and age-matched hospital controls were enrolled. Cases were patients with clinical diagnosis of stroke affirmed by a fellow of the Philippine Neurological Association. Controls were patients admitted to the same hospital with no history of stroke. Consent for the study was taken from all patients.A structured questionnaire was used to determine the following risl factors namely: hypertension, diabetes, transient ischemic attack (TIA), myocardial infarction (MI), atrial fibrillation (AF), rheumatic heart disease (RHD), smoking, frequent alcohol use, habitual snoring, sedentary leisure time physical activity, overweight or obesity manifested by body mass index of 26 and above, migraine, stress, use of contraceptive pills, recent infection represented by history of fever and passive smoking. Measurements for height and weight were done to determine the role of body mass index (BMI) for stroke. Thirty (30) trained research assistants conducted the interview.By univariate matched analysis, the following risk factors were shown to be significant, namely: hypertension, diabetes, TIA, MI, AF, RHD, migraine, habitual snoring, stress, frequent alcohol use, sedentary leisure time physical activity and BMI 26. However, on conditional multiple logistic regression, the following were found to be significant risk factors: hypertension (OR 6.01 95 CI 4.49 - 8.05), diabetes (OR 1.60, 95 CI 1.01 - 2.32), MI (OR 4.67, 95 CI 1.18 - 18.52), current smoking (OR 1.36, 95 CI 1.00 - 1.86), habitual snoring (OR 3.37, 2.49 - 4.58), stress (OR 1.69, 95 CI 1.25 - 2.29) and frequent alcohol use (OR 1.00 95 CI 1.14 - 2.70).The RIFASAF project validates most of the well-established risk factors for stroke cited in foreign studies e.g. hypertension, diabetes, MI, AF, RHD and smoking. In addition, habitual snoring, stress, frequent alcohol intake and sedentary leisure time physical activity are important emerging risk factors that were locally found to be significantly associated with stroke. The results of this nationwide study should encourage local physicians to take particular attention in determining these risk factors among their patients and encourage appropriate risk modification. The RIFASAF study data can be utilized by the Department of Health and the Philippine Neurological Association in their educational campaigns and could be of use in health policy making decisions.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Cerebrovascular disease